CODE SWITCHING IN LONDON LOVE STORY FILM - Ni Luh Desi Meliani (PRASASTI: Journal of Linguistics, 2022)
Code switching is one of the topics that go into sociolinguistics study. This term refers to the phenomenon of language switching, either spoken or written, done by bilingual or multilingual people. In its development, code switching often appears in many literary works, one of them is in London Love Story film. London Love Story is an Indonesian movie released in 2016 by Screenplay Films house production. This movie contains code switching of two languages, Indonesian language and English. This research focused on analyzing the types of code switching which appears in this film which performed by the characters. The result in this research shows there are three types of code switching performed in London Love Story film, namely inter-sentential code switching, tag switching, and intra-sentential code switching refers to types of code switching proposed by Poplack (1980). Eleven utterances categorized into inter-sentential code switching, five utterances categorized into tag switching, and eight utterances categorized into intra-sentential code switching types. This phenomenon is influence by the reasons and social factors of code switching.